Estudo dos recalques do aterro sanitário da Central de Resíduos do Recreio Minas do Leão/RS - Denardin, Gabriela Pippi (2013)
The magnitude and long duration of settlements in municipal solid waste landfills are a major problem in these structures. Several studies and surveys have been developed in recent years to estimate future settlements, based on theoretical or empirical methods. A large number of prediction models for settlements, presented in the literature are based on empirical procedures associated with adjustments to experimental data. Experimental data, in general, are obtained in field monitoring and, to a lesser extent, through studies of compressibility in laboratory large cells. This research aims to contribute with the study of the landfills compressibility through the prediction and monitoring of settlements at the Central de Resíduos do Recreio (CRR), Minas do Leão/RS, through the application of predictive models of existing settlements and verifying the prediction through the monitoring of the actual behavior. In order to achieve this goal it was necessary to apply predictive models of settlements and compare them to see which was best suited to the reality of the landfill. The models used in this research were: Yen and Scanlon Model (1975); Hyperbolic Model of Ling et al. (1998); Creep Model of Edil et al. (1990); Bjarngard and Edgers Model (1990) and Observational Method of Asaoka (1978). To study the compressibility of solid waste, topographic surveys of 6 control points with more significant settlements between 2007 and 2012 (1800 days) in Area 1 of Central de Resíduos do Recreio were used. The employment of the Yen and Scanlon Model (1975), as well as the use of simple logarithmic functions for estimating settlements showed unsatisfactory results. The models proposed by Ling et al. (1998) and Bjarngard and Edgers (1990) were those which presented better results with monitoring data. It is noteworthy that the method of Asaoka (1978) is very interesting for the monitoring of settlements and to verify the stabilization and prediction of the final settlement.